Psychometric Properties of the Acceptance and Action Questionnaire-II in Ecuadorian Adults - Arias, Patricio R. (2023)
Objective. To analyze AAQ-II psychometric properties on the Ecuadorian people. Method. In this study, the psychometric properties of the Acceptance and Action Questionnaire-II (AAQ-II) were evaluated in an Ecuadorian population. A total of 450 people between 18 and 53 years of age, 46.7% of whom were women, participated. Results. The confirmatory factor analysis found a three-dimensional structure: memory avoidance, emotional avoidance, and lack of self-control. An analysis of invariance between men and women revealed that the scale is invariant by sex. The scale was found to have good internal consistency (α = .90). The validity of the AAQ-II as a tool to assess experiential avoidance in an Ecuadorian adult population is discussed.